A Review of Assistive Devices in Synovial Joints: Records, Trends, and Classifications - Filiberto Cruz-Flores; Ana L. Sánchez-Brito; Rafael Campos Amezcua; Agustín Barrera Sánchez; Héctor R. Azcaray Rivera; Arturo J. Martínez Mata; Andrés Blanco Ortega (Technologies, 2025)
This article presents a comprehensive review of assistive devices for synovial joints, addressing their definitions, classifications, and technological advancements. The historical evolution of artificial exoskeletons, orthoses, prostheses, and splints is analyzed, emphasizing their impact on rehabilitation and the enhancement of human mobility. Through a systematic compilation of scientific literature, patents, and medical regulations, the study clarifies terminology and classifications that have often been imprecisely used in scientific discourse. The review examines the biomechanical principles of the musculoskeletal system and the kinematics of synovial joints, providing a reference framework for the optimization and design of these devices. Furthermore, it explores the various types of artificial exoskeletons, and their classification based on structure, mobility, power source, and control system, as well as their applications in medical, industrial, and military domains. Finally, this study highlights the necessity of a systematic approach in the design and categorization of these technologies to facilitate their development, comparison, and effective implementation, ultimately improving users’ quality of life.